How Brexit affects European Union power distribution - László Á. Kóczy (Hungarian Academy of Sciences, Institute of Economics, 2016)
The possible exit of the United Kingdom from the European Union will have profound economic and political effects. Here we look at a particular aspect, the power distribution in the Council of the European Union. Since the Lisbon treaty the exit does not require new negotiations as the success of a voting initiative only depends on the number and total population of the supporting member states. Using the Shapley-Shubik power index we calculate the member states' powers with and without the United Kingdom and update earlier power forecasts using the Eurostat's latest population projections. There is a remarkably sharp relation between population size and the change in power: Brexit increases the largest members', while decreases the smallest ones' powers.
Keywords: C71; D72; 330; European Union; Council of the European Union; qualified majority voting; power index; a priori voting power; demographics